The Features of the Light Scattering Spectral Intensity near the Phase Transition in Crystals of Barium Sodium Niobate - S.D. Tochilin (Журнал нано- та електронної фізики)
Dynamic opalescence, observed in crystals of barium sodium niobate near the point of first-order phase transition, is satisfactorily described by taking into account the spectral interval of its supervision and the spatially inhomogeneous fluctuations of the order.